Identifikasi Bakteri Escherichia Coli Pada Daging Burger Yang Dijual Di Restoran Cepat Saji Di Kota Makassar - Andi Indrawati (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2017)
Burger meat is currently in great demand by the community as one of the food sources of protein. But this burger meat can be contaminated by bacteria, one of which is Escherichia coli. The presence of Escherichia coli in water or food is also considered to have a high correlation with the discovery of disease seeds (pathogens) in food. A study was conducted to identify the bacteria Escherichia coli in burger meat sold in fast food restaurants in Makassar. This research was conducted with several bacteria identification test and also biokima test. Sampling technique is random sampling, with 2 samples from different places. From the results of the tests that have been done, in 2 samples of burger meat, all showed positive results of the presence of bacteria, where the results of biochemical tests showed characteristics of Escherichia coli, so it can be concluded that the two samples of burger meat sold in fast food restaurants in Makassar The presence of Escherichia coli bacteria.